Salmah's entrepreneurial journey with passion, faith, and community support - Mhd. Sarif, Suhaimi; Yahya, Rohaziah; Ismail, Yusof; Abdul Wahid, Mohamad Fikri (IIUM Press, 2024)
Salmah, a young entrepreneur from Batu Gajah, Perak, showcases a compelling journey of passion, resilience, and community collaboration rooted in Islamic values. Despite achieving academic excellence, Salmah chose entrepreneurship over further studies, supported by her mother. Together, they began selling traditional Malay snacks, embodying values like ta'awun (cooperation), taqwa (piety), and tawakal (trust in Allah). Encouraged by customers and friends, Salmah expanded into baking pastries, encountering initial struggles but persevering through patience and gratitude. Her business eventually flourished through community support and participation in local markets. Salmah's story illustrates the power of faith, mutual assistance, and sustainable growth, inspiring others to pursue their entrepreneurial dreams with integrity and dedication.